2011
DOI: 10.1242/dev.059535
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E and CDK-2 regulate proliferative cell fate and cell cycle progression in the C. elegans germline

Abstract: SUMMARYThe C. elegans germline provides an excellent model for analyzing the regulation of stem cell activity and the decision to differentiate and undergo meiotic development. The distal end of the adult hermaphrodite germline contains the proliferative zone, which includes a population of mitotically cycling cells and cells in meiotic S phase, followed by entry into meiotic prophase. The proliferative fate is specified by somatic distal tip cell (DTC) niche-germline GLP-1 Notch signaling through repression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
291
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(344 citation statements)
references
References 64 publications
(85 reference statements)
45
291
2
Order By: Relevance
“…In contrast to regulation of cycling of invertebrate C. elegans and Drosophila premeiotic GSCs, where a G1 is nearly absent and Cyclin E is expressed throughout the cycle, 18,21 we show that O. dioica, pre-meiotic, germline nuclei have a G1-phase. During the period of syncytial germline nuclear proliferation, both the Cyclin Db and Dd variants are expressed.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…In contrast to regulation of cycling of invertebrate C. elegans and Drosophila premeiotic GSCs, where a G1 is nearly absent and Cyclin E is expressed throughout the cycle, 18,21 we show that O. dioica, pre-meiotic, germline nuclei have a G1-phase. During the period of syncytial germline nuclear proliferation, both the Cyclin Db and Dd variants are expressed.…”
Section: Discussioncontrasting
confidence: 86%
“…18,19,21 The O. dioica Cyclin D variants, Da, Db, Dc and Dd are encoded by 4 different genes. 24 Previously, we have shown that O. dioica Cyclin Dd regulates G1-phase in mitotically proliferating cells during early development and in post-metamorphic somatic endocycling cells.…”
Section: Asynchronously Proliferating O Dioica Germ Nuclei Have a DImentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed this number, initially measured by the number of corpses observed at a given time in relation to the number of oocytes that are laid, might be even higher. More recent estimates of germ cell proliferation rates indicate that approximately 20 germ cells are produced every hour, while only ~3 oocytes are laid (Fox et al 2011 ) . Apoptosis only occurs in the female and not in the male germline and is thus only present in hermaphrodites (Gumienny et al 1999 ;Gartner et al 2000 ; ) .…”
Section: Elegans Germ Cell Apoptosismentioning
confidence: 99%
“…Moreover, it supports a differential requirement of GLP-1 activity in cells of the proliferative region. 34 Nonetheless, most likely other target mRNAs of GLD-4-mediated translational activation in transit-amplifying cells and/or GSCs exist.…”
Section: Gld-4 Promotes Proliferationmentioning
confidence: 99%